Construction Of The Sacred In The Moving Image - Gil, Ines (The Turkish Online Journal of Design Art and Communication, 2012)
Contemporary moving image (film and video) is looking for a new form of expressing the sacred, after decades of refusing all kinds of explicit “religious” content. The notion of Sacred changed with the social evolution and today its representation is directly related to the image of reality, that allows a sincere and immediate contact with the viewer. The body’s image can be a strong mediator between the expression of the sacred and reality, because it questions the position of man in the world and its relation to others. Bill Viola and The Dardenne Brothers – among others, are directors who work with a totally different cinematographic form but they have the same challenge: to reveal the potential sacred of life through light and image movement.
Keywords: Film; Sacred; Realism; Body; Film; Kutsal; Realizm; Beden